2022
DOI: 10.1097/j.jcrs.0000000000001032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated lenticular debris on corneal endothelial cells: experimental study in rabbit eyes

Abstract: A study using live rabbits, with subsequent analysis of excised corneas stained with trypan blue/alizarin red, showing simulated swirling lenticular debris may contribute significantly to corneal endothelium damage during phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…26 However, it is noteworthy that the comparison of the results of our study with OVD, with those of the group using simulated lenticular debris but no OVD in our previous study, showed significantly more CEC damage/loss in the no-OVD group (Table 2). 5 OVD is still recommended to minimize CEC damage/loss and prevent subsequent pseudophakic bullous keratopathy, especially for novice surgeons and complicated cases with endothelial corneal pathology, pseudoexfoliation syndrome, traumatic cataracts, hard cataracts, or a history of previous vitreoretinal surgery. 13 Although our study only evaluated 2 OVDs that fit into the categories of cohesive or dispersive, surgical techniques have emerged using combinations of different OVD types (or balanced salt solution and OVDs) to maximize the benefits and minimize the weaknesses of each device.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…26 However, it is noteworthy that the comparison of the results of our study with OVD, with those of the group using simulated lenticular debris but no OVD in our previous study, showed significantly more CEC damage/loss in the no-OVD group (Table 2). 5 OVD is still recommended to minimize CEC damage/loss and prevent subsequent pseudophakic bullous keratopathy, especially for novice surgeons and complicated cases with endothelial corneal pathology, pseudoexfoliation syndrome, traumatic cataracts, hard cataracts, or a history of previous vitreoretinal surgery. 13 Although our study only evaluated 2 OVDs that fit into the categories of cohesive or dispersive, surgical techniques have emerged using combinations of different OVD types (or balanced salt solution and OVDs) to maximize the benefits and minimize the weaknesses of each device.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate swirling lenticular debris, we used the same types of acrylic beads as in our previous study. 5 In brief, the beads were purchased from Hobby Lobby (https://www.hobbylobby.com). Previous characterization of the beads performed through light microscopy, as well as scanning electron microscopy coupled with energy dispersive X-ray spectroscopy, showed the diameter of the acrylic beads to be 0.95 ± 0.07 mm, with the main elemental composition of the surface being carbon, oxygen, aluminum, and titanium.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations